2013
DOI: 10.1158/1078-0432.ccr-13-0314
|View full text |Cite
|
Sign up to set email alerts
|

Variation within 3′-UTRs of Base Excision Repair Genes and Response to Therapy in Colorectal Cancer Patients: A Potential Modulation of microRNAs Binding

Abstract: Purpose: Colorectal cancer is routinely treated with a 5-fluorouracil (5-FU)-based chemotherapy. 5-FU incorporates into DNA, and the base excision repair (BER) pathway specifically recognizes such damage. We investigated the association of single-nucleotide polymorphisms (SNP) in the 3 0 -untranslated regions (UTR) of BER genes, and potentially affecting the microRNA (miRNA) binding, on the risk of colorectal cancer, its progression, and prognosis. SNPs in miRNA-binding sites may modulate the posttranscription… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 42 publications
(53 reference statements)
0
32
1
Order By: Relevance
“…Yoon, K. A et al found that no significant association emerged between this polymorphism and survival of nonsmall cell lung cancer. Further, Pardini et al thought that rs231210 could be a predictor of clinical outcomes in colorectal cancer patients [8]. However, our results suggested that rs231210 was associated with GC susceptibility but not associated with GC prognosis.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Yoon, K. A et al found that no significant association emerged between this polymorphism and survival of nonsmall cell lung cancer. Further, Pardini et al thought that rs231210 could be a predictor of clinical outcomes in colorectal cancer patients [8]. However, our results suggested that rs231210 was associated with GC susceptibility but not associated with GC prognosis.…”
Section: Discussioncontrasting
confidence: 65%
“…Aberrant expression of miRNA may characterize many diseases, including cancer, and these patterns could be used as predictors of susceptibility and prognosis in cancer patients [6, 7]. Various studies have indicated that single nucleotide polymorphisms (SNPs) in the 3′-untranslated region affected the expression levels or the mature sequence of miRNAs and further impacted mRNA and protein expressions [810]. …”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments using cell lines revealed potential functions of some biomarkers, including XRCC3 [50], XRCC2 [58], FGFR4 [66], and NF-κB [75], in chemoradiation sensitivity. Interestingly, two nCRT-responsive SNPs located in miRNA target sites of the MRE11A gene (rs2155209) [140] and the SMUG1 gene (rs2233921) [141] affected gene transcription. Although miRNAs that target these SNPs were not identified, the results suggested potential biological links of these SNPs to nCRT response.…”
Section: Discussionmentioning
confidence: 99%
“…Vymetalkova et al examined 13 SNPs in predicted miRNA target sites in mucin genes in 310 rectal cancer patients and the patients with CC genotype of rs4729655 in mucin 17 ( MUC17 ) gene exhibited a longer overall survival (hazard ratio = 0.27, 95% CI = 0.14–0.54, p < 0.001) than those without CC genotype [139]. The same research group also identified significant association of overall survival in CRC with SNPs located in miRNA target sites of DNA repair protein RAD52 homolog ( RAD52 ) (rs11226), X-ray repair cross-complementing protein 5 ( XRCC5 ) (rs1051685) and single-strand-selective monofunctional uracil-DNA glycosylase 1 ( SMUG1 ) (rs2233921) [140,141]. …”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…Concerning the most commonly used therapies based on 5-fluorouracil (5-FU), miRSNPs in BER genes were evaluated, and interesting results were found for miRSNPs rs1534862 within NEIL2 and rs223392 within SMUG1 57. Both miRSNPs were found to be associated with OS, with the stronger association for TT homozygotes of rs223392 after stratification for 5-FU-based chemotherapy.…”
Section: Colorectal Cancermentioning
confidence: 99%